Violation of the Refugee Convention and the Compliance of Ratified Countries - Siahaya, Tirza; Wattimena, Josina Augustina Yvonne; Daties, Dyah Ridhul Airin (Fakultas Hukum Universitas Pattimura, 2026)
Introduction: Starting the internal conflict of the refugee crisis, Syria as a refugee country which is a domino effect of the Arab Spring phenomenon where the conditions of the Arab countries began the transition from a country with a monarchical system to a democratic system, making Syria one of the largest refugee countries heading to the European Union through Greece. However, Greece's refusal to allow Syrian refugees to enter Greece has led to Greece being found to have expelled and rejected refugees who attempt to enter Greece.Purposes of the Research: Examine and understand the binding force of the Convention Relating to the Status of Refugees 1951 according to international treaty law. Examine and know the responsibility of States that have ratified the Convention Relating to the Status of Refugees 1951, but do not carry out their responsibilities.Methods of the Research: Using exploratory normative research methods, the problem approaches used are the statute approach, the theoretical approach, and the case approach. The sources of legal materials in this writing are primary, secondary and tertiary legal materials. The technique of collecting legal materials uses a literature study which is then analyzed qualitatively to answer the problems studied.Results of the Research: The responsibility and compliance of the Greek State that has ratified the Convention Relating to the Status of Refugees 1951 towards refugees. Violating an important responsibility regarding refugees is the principle of non-refoulement which prohibits the State from expelling or forcing refugees back where the refugees would face threats to the life and freedom of the refugees. Greece as a party to an international treaty cannot give a reason for not complying with a treaty for national reasons. This makes Greece not comply with and fulfill the obligations of a mutually agreed agreement. Countries that have ratified have a much greater responsibility in their efforts to handle and protect refugees.